Assessment of the effect of snakebite on health and socioeconomic factors using a One Health perspective in the Terai region of Nepal: a cross-sectional study. Issue 3 (March 2022) - Babo Martins, Sara; Bolon, Isabelle; Alcoba, Gabriel; Ochoa, Carlos; Torgerson, Paul; Sharma, Sanjib K; Ray, Nicolas; Chappuis, François; Ruiz de Castañeda, Rafael
Summary: Background: Snakebite envenoming has a substantial health and socioeconomic effect in rural communities. However, there are insufficient epidemiological and animal data, which prevents accurate assessment on the effects of snakebite. We aimed to assess the health and socioeconomic effect of snakebite using a One Health perspective. Methods: In this cross-sectional survey-based study, we assessed the health and socioeconomic effects of snakebite data using a multicluster survey that was previously done as part of the SNAKE-BYTE project in the Terai region, Nepal. Health effect was measured in terms of disability-adjusted life years (DALYs). Livelihood losses encompassed out-of-pocket health-care expenditures, losses of productivity due to days off work, and the losses due to mortality and treatment costs in domestic animals. Mortality losses in domestic animals were also estimated as animal loss equivalents, and overall human and animal health effect expressed using modified DALYs for zoonotic disease (zDALYs). Findings: We estimate an annual snakebite burden of 200 799 DALYs (95% CI 103 137–357 805), mostly due to mortality in children and women. Snakebite is estimated to lead to US2·8 million in yearly livelihood losses associated with human and animal cases. Overall, we estimate a yearly human and animal health burden of 202 595 zDALYs (104 300–360 284). Interpretation: These findings present robust evidence on the extent of snakebite's health and socioeconomic effect and emphasise the need for a One Health perspective. The results also stress how improved data collection at the community level is crucial for improved assessments of its effect. Funding: Swiss National Science Foundation.